Measuring civil engineers' level of engagement in the South African construction industry . - Klopper, Dirk Reynard (My University, 2017)
There is a great need for professionalism and ethical rigour within the South African construction industry. Civil engineers prove themselves true custodians of the construction environment and yet those that work full-time on site are in short supply. This study, however, assumes that the pressing demands of the job, the long working hours and the unprecedented pressures are not the only factors that discourage civil engineers to work as construction engineers on site. This research therefore aims to compare the level of engagement of consulting engineers and construction engineers in the South African construction industry to establish the different psychological experiences between the two roles. The data needed for the study was collected using an open questionnaire. A Likert- Scale was used to establish the survey participant’s degree to which they agree or disagree with given statements. These statements were worded upon three different underlying constructs of Employee Engagement: Meaningfulness, Psychological Safety and Psychological Availability – under which the conclusions were made. It was found that construction engineers (engineers that manage the construction of a project) are more commitment to their tasks than consulting engineers (regardless of their psychological condition). They devote higher levels of physical energy, emotional connection and cognitive focus than consulting engineers. Also, construction engineers show a significantly higher level of Meaningfulness in their roles than consulting engineers because they scored higher levels of job satisfaction by showing higher means for task significance and task identity. Construction engineers show thus higher levels of work engagement and not employee engagement. Also, it was found that consulting engineers show significantly higher levels of Psychological Availability and Psychological Safety in their roles than construction engineers, especially those that spend less than 50% of their time onsite. Consulting engineers have the necessary job resources in the form of supervisor support and job security, which support their work goals, personal growth, learning and development. Construction engineers experience higher levels of job demands and are thus more likely to experience overburdening and exhaustion than consulting engineers in the form of physical, emotional and cognitive strain. Additionally, construction engineers experience a higher impact on their social lives. The level of Engagement of consulting engineers is clearly different from the level of Engagement of construction engineers. However, there is a lack of understanding of the construction business and the modern demands and challenges faced by engineers in construction that creates a negative perception towards to industry. The results show that there are both pros and cons to working as consulting and construction engineers and that there is much that engineering companies can do to aid in engaging and retaining their engineers.
MBA Thesis
Keywords: Employee motivation -- South Africa,Construction industry -- South Africa,Consulting engineers -- South Africa,Civil engineers -- South Africa